General Question

Sapphire_Frenzy's avatar

Algebra problem: Can you help?

Asked by Sapphire_Frenzy (90points) October 6th, 2012

Afternoon, I’m just doing a bit of algebra revision on the BBC GCSE Bitesize website and one question has stumped me: I can’t figure out where I’m going wrong.

Here is the question:

4. If a = b – c, then:

a. c = b – a
b. c = a + b
c. c = a – b

Apparently a is the right answer, but I can’t work out how to get there.

I’ve been taught that when letters/numbers change sides they change their sign as well, therefore I answered b.

Any help is appeciated :) (I could just ask my Maths teacher on Monday but I’m rather impatient)

Observing members: 0 Composing members: 0

8 Answers

yankeetooter's avatar

Yes, but “a” changed sides as well; therefore it would be negative in the answer…

flutherother's avatar

Yes, as above. -c =a – b therefore +c= -a +b

dabbler's avatar

Add C to both sides and subtract A from both sides, voila !
Keep in mind that you can do whatever you want to one side of the equation as long as you do the exact same operation to the other side.

CWOTUS's avatar

Welcome to Fluther.

@dabbler has given you the correct answer and the methodology.

Sapphire_Frenzy's avatar

Ah right I see where I was going wrong now. Thank you.

PhiNotPi's avatar

The above answers are correct. I’ll now show it in even more detail.

a = b – c
a + c = b – c + c
a + c = b
a + c – a = b – a
c = b – a

LostInParadise's avatar

You can always substitute numbers to check your answer.
if a = 7, b = 10 and c = 3 then the answers says 3 = 10 – 7

On a multiple choice test, you can use this approach to get the answer by process of elimination, but I would not recommend doing that.

gasman's avatar

I’ve been taught that when letters/numbers change sides they change their sign as well… Not a very reliable rule, as you’ve already seen. A better rule, which you can always count on, is that you must perform the same operation on both sides of the equals sign – as mentioned by @dabbler.

In this problem, a = b – c, you can add c to both sides, then subtract a from both sides, to arrive at the result c = b – a.

Answer this question




to answer.

This question is in the General Section. Responses must be helpful and on-topic.

Your answer will be saved while you login or join.

Have a question? Ask Fluther!

What do you know more about?
Knowledge Networking @ Fluther